Profitability of production and resource-use efficiency among ofada rice (Oryza sativa japonica) farmers in Southwest, Nigeria - Omonona, Bolarin Titus; Lawal, Justina Oluyemisi; Oyebiyi, Ifeoluwa Damilola (Comunicata Scientiae, 2012)
Ofada rice has recently gained prominence and it is quickly drawing international attention since it has revealed a strong consumer disposition and it has been perceived to be more nourishing due to its natural taste, a value added to this kind of rice. Nigeria has potential to produce it to self-sufficiency level but due to the inefficient use of inputs and in-availability of some inputs, this has become a mirage. Data was obtained from 180 rice farmers selected from the rice growing areas in Ogun state, with the use of well structured questionnaire. The data collected were then analyzed using both descriptive and inferential statistics. The descriptive analysis showed that 70% of the farmers were males, the average age and farm size was 45years and 2.9ha, respectively. The maximum likelihood estimates of the stochastic production frontier model results showed that a unit increase in farm size, labour, seeds and chemicals used will result in extra 64.587kg, 3.98kg, 0.54kg, and 2.258kg of the output, respectively. Marginal value product (MVP) to the unit prices for these inputs was greater than one implying that all these resources were underutilized. The gross margin analysis revealed that the profit from rice farming was N56, 082 (US$373.88) per hectare per farmer. Farmers’ efficiency can be enhanced by increasing the area of land cultivated, labour used, quantity of seeds and chemicals used for production.